Bone-in pork loins: modified atmosphere packaging to extend shelf-life - K E Warren; Melvin C Hunt; C L Marksberry; O Sorheim; Donald H Kropf (Kansas Agricultural Experiment Station Research Reports, 1990)
Modified atmosphere packaging with 100% carbon dioxide was used to investigate changes in daily gas composition, as well as the influence of fat trim level and location of loin in the box on shelf life characteristics. Length of storage was the primary factor influencing shelf life of whole loins and their retail chops. Although microbial qualities was acceptable in loins stored up to d 19, sirloin and blade discoloration was obvious at 11-13 d. Storage for more than 11 d reduced the display life of retail chops to 1-2 d. Shelf life characteristics of bone-in pork loins were superior with this packaging system compared to more traditional systems.; Swine Day, Manhattan, KS, November 15, 1990
Keywords: Swine day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-189-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 610; Swine; Pork; Packaging; CO2; Shelf-life; Color